Blood Donation – Incentives and Inducements: where to draw the line?. (10th November 2019) - Flanagan, Peter
Abstract : The ISBT Code of Ethics (the Code) identifies that blood donation should be voluntary and non‐remunerated (VNRD). Blood Services need to ensure that sufficient suitable donors are available to meet the clinical needs of the patients and hospitals that they support. In an increasingly busy world, Blood Services need to compete with other organizations promoting community health and well‐being in order to achieve this. Promotional and marketing activities are utilized to both attract new donors and to encourage repeat donation from regular donors. In designing programmes to improve recruitment and retention of donors, consideration needs to be given to both the effectiveness of the intervention and also whether the activities might inadvertently breach the principles underpinning VNRD. The available evidence relating to the effectiveness of incentives to donation is limited and there is a need for more active research in this area.